How Should We Treat Patients with Mild Asthma? - Wong, Gary W.K (The New England journal of medicine, 2019)
Asthma is one of the most common chronic respiratory diseases in the world. Despite advances in the understanding of the biologic characteristics of asthma and its treatment, many surveys continue to document suboptimal control in large proportions of patients around the world. 1,2 Both U.S. and international guidelines recommend the use of short-acting β 2 -agonists (SABAs) as needed for the treatment of mild intermittent asthma. 3,4 When symptoms become persistent, the recommended treatment is an inhaled glucocorticoid taken on a regular basis, so-called maintenance therapy, which should lead to reduced use of a SABA. In reality, patients tend to rely on as-needed SABAs . . .